Avaliação da lipocalina associada à gelatinase de neutrófilos (NGAL) em idosos após osteossíntese de fêmur - Andrade Neto, José de Souza [UNESP] (2015)
Introduction: Introduction: Acute kidney injury is common in hospitalized patients undergoing surgical procedures. It is responsible for a high mortality and yet, there is no early and reliable diagnostic marker. Elderly patients are at risk and often undergo orthopedic procedures as surgical repair of femur fractures. Objectives: To evaluate serum NGAL as a predictor of AKI in the postoperative correction of femur fractures in the elderly. Methodology: 56 elderly patients undergoing surgical repair of femoral fracture were studied prospectively for 48 hours postoperatively. Blood samples were collected for analysis of NGAL after surgery, 4 and 24 hours later. Creatinine measurements collected 24 and 48 hours postoperatively. Accuracy of NGAL was analyzed for diagnosis of acute kidney injury. Results: 16 (28.1%) of patients developed AKI and had significantly higher values of serum NGAL. In 4hours the AUROC = 0799 (0663-0936, p <0.001). In 24 hours the AUROC = 0.805 (0665-0946, p <0001). Conclusion: The molecule of NGAL showed good accuracy for prediction of AKI within 24 hours when measured after 04 hours and 24 hours postoperatively